SOSIALISASI DAN PENDAMPINGAN PEMBUATAN PUPUK ORGANIK CAIR (POC) DARI LIMBAH JAMBU METE MENGGUNAKAN METODE EMBER BERTUMPUK - Humaira, Ani Fatin; Sasmita, Anggi; Putri, Fadila Rahmatika; Khantasilo, Ananda; Ramdani, Rifki; Putri, Rizky Emayantiara; Rozaldi, Osama Riza; Osama Riza Rozaldi; Jamadi, Yasin; Nurardianingsih; Solihin; Liaturrahman, Noval; Yasa, I Wayan (Universitas Mataram, 2024)
Selengen Village is one of the villages in Kayangan District, North Lombok Regency which has abundant potential for plantation and agricultural products. One of the existing plantation products is cashew nuts. Abundant plantation products also result in high levels of plantation product waste which cannot be managed optimally by local communities. One effort that can be done is processing waste into organic fertilizer. For this reason, the PMD KKN team from Mataram University, Selengen Village, held a socialization regarding the manufacture of Liquid Organic Fertilizer (LOF) with the aim of utilizing plantation waste in the hamlet of Tangga, Selengen village. There were two methods used, namely socialization and direct practice involving the community members. farmers in the hamlet of Tangga Selengen Village. The activity was carried out on January 16 2024 in Tangga Hamlet, in collaboration with the North Lombok Regency Environment and Forestry Service (DLHK) as presenters and KKN students as demonstrators of the stages of making a LOF. From this activity, the output was obtained in the form of tools for making liquid organic fertilizer, namely stacked buckets and Liquid Organic Fertilizer (LOF) products from cashew nuts. The resulting LOF can be utilized and applied by spraying it on plant leaves. After the entire series of events had been carried out, the event was closed by the presenter and ended with a group photo and distribution of POC products by KKN students to the participants. Socialization and education regarding the management of plantation waste into products must continue to be carried out. This is to increase community knowledge and habit in managing existing waste, as well as increase community consistency in protecting the environment.